Investigation of Corrosion Behavior of Bioactive Coverings on Commercially Pure Titanium and its Alloys - M.Yu. Gazizova; M.B. Ivanov; T.N. Vershinina (Журнал нано- та електронної фізики)
A microporous and macroporous bioactive coatings on boimedical titanium alloys (VT1-0, VT6, Ti-6Al-7Nb) were formed by a micro-arc oxidation method. The effect of the phase composition of microporous and macroporous coatings on corrosion behavior titanium and its alloys was investigated. The results show that phase composition of the coatings microporous presented only titanium oxides: anatase and rutile, at that the phase composition macroporous coatings consists of anatase, rutile and calcium phosphate compounds: tricalcium phosphate (TCP) α-Ca3(PO4)2 and calcium deficient hydroxyapatite Ca9HPO4(PO4)5OH. Corrosion behavior of MAO coatings was investigated in solution 0.9 % NaCl using potentiodynamic polarization tests. The microporous coatings exhibited a more highest corrosion resistance than macroporous coatings, it is connected with containing calcium phosphate compounds in macroporous coatings.